INOVASI MINUMAN HERBAL MIDANG UNTUK MENINGKATKAN NILAI TAMBAH TANAMAN OBAT KELUARGA DAN KESEHATAN MASYARAKAT DESA GONDANG KECAMATAN GANGGA KABUPATEN LOMBOK UTARA - Astuti, Nanik Nia Puji; Cahyani, Utari Nur; Rahmi, Ulya; Sriasih, Made (Universitas Mataram, 2024)
Herbal drinks have become a popular alternative in maintaining people's health and well-being, especially in the modern era filled with the need for a healthy lifestyle. In Gondang village, Gangga sub-district, North Lombok district, the abundant potential of family medicinal plants (TOGA) has not been fully utilized. To address this challenge, an innovative herbal drink for Gondang village (MIDANG) aimed at increasing the added value of TOGA and improving public health was introduced to the Gondang village community. With a holistic approach, this activity covers the technical aspects of MIDANG production and the socio-economic implications of this product development. It is hoped that the MIDANG Herbal Drink will be a positive step towards sustainable prosperity for the people of Gondang Village and its surroundings.